2017
DOI: 10.1080/10717544.2017.1410257
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsion-based delivery system for enhanced oral bioavailability and Caco-2 cell monolayers permeability of berberine hydrochloride

Abstract: Berberine hydrochloride (BBH) has a variety of pharmacological activities such as antitumor, antimicrobial, anti-inflammation, and reduce irritable bowel syndrome. However, poor stability and low oral bioavailability limited its usage. Herein, an oil-in-water nanoemulsion system of BBH was developed to improve its stability and oral bioavailability. The pseudoternary phase diagrams were constructed for the determination of composition of various nanoemulsions. The nanoemulsions of BBH composed of Labrafil M 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…In cellular models using HepG2 cells, targeting proprotein convertase subtilisin/kexin type 9 (PCSK-9) by this nanoparticle preparation to lower low-density lipoprotein cholesterol (LDL-C) has been presented. Nanoemulsion-based delivery systems with a significant increase in intestinal permeability as assessed by Caco-2 cell monolayers and a significant reduction in efflux have also been shown by Li et al [46]. The study by Xie et al [47] further showed that berberine nanoparticles were effective in ameliorating ischemia-reperfusion injury in renal tubular epithelial cells.…”
Section: Figurementioning
confidence: 74%
“…In cellular models using HepG2 cells, targeting proprotein convertase subtilisin/kexin type 9 (PCSK-9) by this nanoparticle preparation to lower low-density lipoprotein cholesterol (LDL-C) has been presented. Nanoemulsion-based delivery systems with a significant increase in intestinal permeability as assessed by Caco-2 cell monolayers and a significant reduction in efflux have also been shown by Li et al [46]. The study by Xie et al [47] further showed that berberine nanoparticles were effective in ameliorating ischemia-reperfusion injury in renal tubular epithelial cells.…”
Section: Figurementioning
confidence: 74%
“…The efflux ratio of BBR SNE was 2.47 ± 0.47, suggesting the presence of an efflux transporter. In addition, the apparent permeability coefficient (Papp) values of BBR from A-to-B transport and from B-to-A efflux were summarized [ 27 ]. The permeability coefficients of BBR and BBR SNE with verapamil, a P-glycoprotein inhibitor, were significantly lower than with BBR, which indicated that BBR SNE reduced BBR efflux in Caco-2 cell monolayers, and the drug was probably effluxed by P-glycoprotein.…”
Section: Resultsmentioning
confidence: 99%
“…The previously reported reasons for poor membrane permeability, low bioavailability and poor stability of berberine were, low apparent oilwater partition coefficient (IgPapp = ˗ 1.08), presence of hydrophobic properties like two methoxy groups and a quaternary ammonium cation in its structure that shows high affinity to the multidrug efflux pump P-gp in gastrointestinal system. Berberine was reported to be a substrate of P-gp efflux pump 23,24 . In caco-2 cell line study, it was reported that, when synthetic P-gp inhibitors like cyclosporine and verapamil were coadministered with berberine, there was marked enhancement in the absorption of berberine, 18 indicating involvement of P-gp pump in the efflux of berberine into the intestinal lumen, leading to poor absorption and thus low bioavailability 24 .…”
Section: Methodsmentioning
confidence: 99%